TINGKAT KESUKAAN PANELIS TERHADAP PENYEDAP RASA ALAMI HASIL SAMPING PERIKANAN DENGAN EDIBLE COATING DARI KARAGENAN - Djohar, M. Alaksmar; Timbowo, Semuel Marthen; Mentang, Feny (Media Teknologi Hasil Perikanan, 2018)
Â Product of fish procecing industry called â€œjuice waterâ€ contain a lot amino acid compound. The aim of this study was analyze sonsory characteristic of natural condiment made fromâ€ juice waterâ€ by product of fishery industry , coatedÂ  with karagenan edible. The method of this study of natural condimenent coated karagenan coating where assessed by trained panelis using by sensory attributes (odor, colour apparance andÂ  taste).The result indicate potencial of natural condiment for seasoning development.This research aims to be able to produce natural flavor that made from raw material of liquid waste of stew and coating with edible coating of carrageenan. A natural flavor enhancer, as a food additive, needs to be done a hedonic organoleptic analysis to see the panelist's preference for natural flavorings. The results of a hedonic organoleptic test show that taste and odor are preferred over the texture and appearance of the natural flavorings.